O turismo e as transformações socioambientais no litoral do Iguape-Aquiraz-CE - Carneiro, Tatiane Rodrigues (2010)
The subject of this work was the coastal district of Iguape located in the city of Aquiraz, east coast of Ceará, 38 km from Fortaleza. In recent years, there has been a change in tourism demand in that region and increased investment by both the public and private capital and international levels. Tourism is an economic activity that transforms space and reorganizes the territories and at the same time, generates social and environmental impacts to the cities where it develops. Thus, this study sought to understand the social and environmental changes of tourism on the coast of Iguape, characterizing their social and environmental conditions, and propose measures to achieve sustainable tourism in the region. For a better understanding of the environmental changes of the Iguape coastline, it was divided into: Presídio´s beach, Iguape´s beach and Barro Preto´s beach, because they are most relevant in terms of tourism. Throughout this study were used concepts such as tourism, tourist attraction, tourist offer, tourist services, sustainable tourism, sustainable development, environment, landscape and environmental perception. The research was accomplished through reference books, observations, field surveys, questionnaires and interviews with local people, entrepreneurs, tourists and visitors being held at two different times, first in libraries, public agencys and then on the spot . From the interviews and questionnaires it was possible to better understand the view of tourists, residents and entrepreneurs on tourism held in the region, these often contradictory opinions, and understand the social and environmental transformations generated there by offering up alternatives to the achievement of sustainable tourism, like a global and participatory planning of tourism at the coast.